Determinants of e-commerce adoption in Kuala Lumpur: testing the mediation effects of perceived ease of use nd perceived usefulness - Ciputra, Tanaka (2023)
The research topic is “Determinants of E-Commerce Adoption in Kuala Lumpur: Testing theMediation Effects of Perceived Ease of Use and Perceived Usefulness”. Moving forward, commerce has developed to the point where it is no longer required to view the productfirst-hand to make a rational purchasing decision. Consumers tend to look for new purchasing methods that will provide them with a higher degree of customisation, or one thatthey find most convenient. Furthermore, the current pandemic case has become an accelerator for the Digital Economy, and contactless transactions.In order to handle the newfound demands and issues of the consumers, vendors must replan their business models to cater to their needs, to ensure that they are able to stay ahead in the market. With that in mind, several vendors have opted to lean towards online marketing. This has led to the development of the digital economy. The digital economy has affected the economy in multiple aspects, whether it may be through improvement, or additional threats. The objective of this research is to study the relationship between the adoption rate of e-commerce, and the influential factors of the digital economy that is related to it. This research will help researchers determine and predict the future growth of the e-commerce platform. The influential factors of the digital economy that will be researched upon this topic are perceived usefulness, perceived ease-of-use, facilitating conditions, subjective norms, and perceived risk, which are the factors of the Digital Economy that will be observed.